Strong spin Seebeck effect in Kondo T-shaped double quantum dots. (12th December 2016) - Wójcik, K P; Weymann, I
Abstract: We investigate, taking a theoretical approach, the thermoelectric and spin thermoelectric properties of a T-shaped double quantum dot strongly coupled to two ferromagnetic leads, focusing on the transport regime in which the system exhibits the two-stage Kondo effect. We study the dependence of the (spin) Seebeck coefficient, the corresponding power factor and the figure of merit on temperature, leads' spin polarization and dot level position. We show that the thermal conductance fulfills a modified Wiedemann–Franz law, also in the regime of suppression of subsequent stages of the Kondo effect by the exchange field resulting from the presence of ferromagnets. Moreover, we demonstrate that the spin thermopower is enhanced at temperatures corresponding to the second stage of Kondo screening. Very interestingly, the spin-thermoelectric response of the system is found to be highly sensitive to the spin polarization of the leads. In some cases spin polarization of the order of 1% is sufficient for a strong spin Seebeck effect to occur. This is explained as a consequence of the interplay between the two-stage Kondo effect and the exchange field induced in the double quantum dot. Due to the possibility of tuning the exchange field by the choice of gate voltage, the spin thermopower may also be tuned to be maximal for desired spin polarization of the leads. All calculations are performed with the aid of the numerical renormalization group technique.